Challenges for Peacemakers: How to Overcome Socio-Psychological Barriers. (October 2014) - Hameiri, Boaz; Bar-Tal, Daniel; Halperin, Eran
Resolving intergroup conflicts is one of humanity's most important challenges. Social psychologists join this endeavor, not only to understand the psychological foundations of intergroup conflicts but also to suggest interventions that aim to resolve conflicts peacefully. The present article begins by describing a specific type of conflict, namely, an intractable conflict that has distinguishing characteristics. One characteristic that fuels its intractability is the presence of socio-psychological barriers. These barriers result in one-sided information processing that obstructs the penetration of new information to promote peace: Members of a society immersed in an intractable conflict are frozen in their conflict-supporting societal beliefs. The most challenging question is how to unfreeze these beliefs, to overcome these barriers. Various interventions have been designed to promote intergroup peace, within a new taxonomy specifying the nature and goals of the interventions. Peace-promoting interventions can be divided into three categories: (a) interventions that provide contradictory information, (b) interventions that provide information through experiences, and (c) interventions that teach a new skill. Finally, a number of conclusions and limitations stem from the reviewed interventions, suggesting a new line of intervention based on "paradoxical thinking."